228 GROUP VISITS: IF YOU BUILD IT, WHO WILL COME?. (1st January 2005) - Kawasaki, L.; Muntner, P.; Hampton, K.; DeSalvo, Sanne. S. K.B.
Abstract : Background: Group visits are an interactive, patient-centered model of care with demonstrated benefit in the management of chronic disease. The success of this model is dependent upon patient recruitment, yet little is known about predictors of participation. Objective: We studied correlates of willingness to attend group visits for the treatment of hypertension in a population of urban, disadvantaged patients. Methods: One trained interviewer surveyed 206 patients by telephone from a list of eligible candidates for a randomized trial comparing group visits versus individual care in the treatment of hypertension. The validated survey included questions about demographics, medical history, psychosocial parameters and experiences with health care. Results: Most participants were female (80%) and black (89%) with a mean age of 56 years (SD ± 9.9) and an income of less than 1000/month (75%). 30% had a diagnosis of hypertension for more than 10 years and 92% reported a family history of hypertension. 56% had hyperlipidemia; 34% currently smoked; 30% had diabetes; and fewer than 10% had a history of MI or CVA. 69% reported a willingness to attend group visits for their hypertension care. Patients with diabetes, longer duration of hypertension, and better experience with care tended to be more willing to participate in group visits, though these differences were not significant. Those with less than an 8th grade education were less likely to express willingness to attend (p < .05). In a multivariable logistic model adjusting for age, significant predictors of willingness to attend group visits included an income > 1000 (OR 2.6, CI 1.1-6.1); poor self-rated health (OR 25.4, CI 1.7, 382.9); desire to spend more time with their physician (OR 1.7, CI 0.9, 3.3); and rarely waiting after check-in for their physician appointment (OR 1.9, CI 1.0-3.6). Those not willing to participate indicated that a reduced wait time to see the physician (40%), more time with their physician (30%) and parking/transportation subsidies (28%) would provide incentive to attend a group visit. Conclusions: The vast majority of these socioeconomically disadvantaged patients were interested in participating in group visits for their hypertension treatment. Simple incentives and targeted promotion may enhance recruitment. Group visits appear to be an acceptable and viable alternative model of chronic disease care in vulnerable populations.